Islamic finance and the convergence towards International Financial Reporting Standards (IFRS): the state of research development - Mulyany, Ratna; Mohd Ariffin, Noraini (University of Syiah Kuala, Banda Aceh, Indonesia, 2018)
Extensive research has been undertaken in the area of accounting harmonization ever since the idea of harmonizing accounting standards and practices was probably initiated as early as 1930s. The transformation of International Accounting Standard Committee (IASC) into International Accounting Standard Board (IASB) in 2001, which refines the harmonization agenda into convergence initiative, has escalated the academic research devoted in this field. Nevertheless within the broad research theme of International accounting harmonization and convergence (IAHC), quite limited studies have looked at the issues of IAHC and linking it to the development of Islamic banking and finance. Not until recently where quite significant acknowledgement has been given on this issue especially by the industry community, the earlier development of research in IAHC has not sufficiently covered the interaction between IAHC and the Islamic financial industry. Departing from this context, this paper aims to review the development of research that particularly looked into the issues of IAHC in relation to the Islamic financial industry.